Optimal Maturity Structure of Sovereign Debt in Situation of Near Default - Desgranges, Gabriel; Rochon, Celine (Washington, D.C. : International Monetary Fund, 2014)
We study the relationship between default and the maturity structure of the debt portfolio of a Sovereign, under uncertainty. The Sovereign faces a trade-off between a future costly default and a high current fiscal effort. This results into a debt crisis in case a large initial issuance of long term debt is followed by a sequence of negative macro shocks. Prior uncertainty about future fundamentals is then a source of default through its effect on long term interest rates and the optimal debt issuance. Intuitively, the Sovereign chooses a portfolio implying a risk of default because this risk generates a correlation between the future value of long term debt and future fundamentals. Long term debt serves as a hedging instrument against the risk on fundamentals. When expected fundamentals are high, the Sovereign issues a large amount of long term debt, the expected default probability increases, and so does the long term interest rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet